KIKUCHI DISEASE WITH ASSOCIATED SYSTEMIC LUPUS ERYTHEMATOSUS: A CASE REPORT - Irshad, Shadman; Khan, Majid; Akbar, Saeed; Ajmal, Fahad; Jan, Muhammad Abdullah; Arshad, Fahad (Journal of Postgraduate Medical Institute, 2011)
This case report describes a 28 year old male patient presenting with low-grad fever, symmetrical polyarthritis, rash on palms, neck and trunk, oral ulcers and cervical, axillary and hilar lymphadenopathy. Other systemic examination was unremarkable. Patient was diagnosed as Kikuchi-Fujimoto's disease on the basis of lymph node histopathology, which showed the pathognomonic "Acute Histiocytic Necrotizing Lymphadenitis". Concurrently diagnosis of systemic lupus erythematosus (SLE) was also made because of the presence of five out of eleven criteria for the diagnosis of SLE. The five criteria which were present in this patient were oral ulcers, arthritis, proteinuria of 1295 mg/24 hrs, positive Antinuclear Antibody and positive anti-double stranded DNA.